Antimicrobial Prophylaxis and Its Association with Surgical Site Infection in General Surgery Patients: A Secondary Data Analysis at Universitas Airlangga Hospital - Ricky Wibowo (Universitas Airlangga, 2026)
Introduction: Surgical site infection (SSI) occurs within 30 days after surgery or within 90 days if an implant is used. Appropriate surgical antimicrobial prophylaxis reduces SSI risk, while inappropriate use may promote antimicrobial resistance. This study evaluated SSI incidence and adherence to guideline, recommended prophylactic antibiotic practices. Method: A A retrospective observational study was conducted using secondary data from adult patients undergoing general surgery at Universitas Airlangga Hospital (March–June 2025). Antibiotic selection, dosage, route, timing, and duration were assessed according to the hospital PPAB, ASHP guideline, and Indonesian Ministry of Health Regulation No. 28/2021. Associations with SSI were analyzed using Fisher’s exact test. Results: A total of 87 patients were included in the analysis. Cefazolin was the most frequently prescribed prophylactic antibiotic (82.76%), followed by ceftriaxone (17.24%). Compliance with guideline recommendations was achieved for antibiotic dosage, route of administration, and duration in all patients, whereas only 35.63% received prophylactic antibiotics within the recommended 30-60 minute interval before surgical incision. The overall incidence of SSI was 2.30%. No Significant association was observed between the timing or duration of prophylactic antibiotic administration and SSI occurrence (p>0,05). Among the evaluated patient and surgical characteristics, only ASA physical status classification was significantly associated with SSI (p=0.018). Conclusions: Surgical antimicrobial prophylaxis at Universitas Airlangga Hospital generally adhered to guidelines for dosage, route, and duration, with a low SSI incidence. However, adherence to recommendations for antibiotic selection and timing of administration should be improved. Strengthening compliance with evidence-based protocols may further enhance antimicrobial stewardship and reduce SSI risk.